Prevalence of Metastatic Neck Nodes (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Head and neck cancers include cancers of the lips, mouth, nasal cavity, paranasal sinuses, pharynx and larynx. Most of these cancers are squamous cell carcinomas (SCCs). The presence of metastatic cervical lymphadenopathy is of particular importance as with every single nodal metastasis, survival of the patient is reduced by one half.Objective: To see the prevalence of metastatic neck node.Methods: The prospective cross-sectional clinical study was carried out in the Department of ENT and Head Neck Surgery, Combined Military Hospital, Dhaka during March’2018 to March, 2019. All 100 patients were included in this study and were treated at the Department of Otolaryngology of Combined Military Hospital, Dhaka.Results: Total 26 cases were found parotid among them 8(30.8%) in metastatic neck node and 18(69.2%) in without metastatic neck node. Total 10 cases were found paranasal sinuses among them 1(10.0%) in metastatic neck node and 9(90.0%) in without metastatic neck node. Which were statistically significant (p